Light absorption of organic carbon and its sources at a southeastern U.S. location in summer. (January 2019) - Xie, Mingjie; Chen, Xi; Holder, Amara L.; Hays, Michael D.; Lewandowski, Michael; Offenberg, John H.; Kleindienst, Tadeusz E.; Jaoui, Mohammed; Hannigan, Michael P.
Abstract: Light-absorbing organic carbon (OC), also referred to as "brown carbon" (BrC), has been intensively investigated in atmospheres impacted by biomass burning. However, other BrC sources (e.g., secondary formation in the atmosphere) are rarely studied in ambient aerosols. In the current work, forty-five PM2.5 filter samples were collected in Research Triangle Park (RTP), NC, USA from June 1st to July 15th, 2013. The bulk carbonaceous components, including OC, elemental carbon (EC), water soluble OC (WSOC), and an array of organic molecular markers were measured; an ultraviolet/visible spectrometer was used to measure the light absorption of methanol extractable OC and WSOC. The average light absorption per OC and WSOC mass of PM2.5 samples in summer RTP are 0.36 ± 0.16 m 2 gC −1 and 0.29 ± 0.13 m 2 gC −1, respectively, lower than the ambient aerosol samples impacted by biomass burning and/or fossil fuel combustion (0.7–1.6 m 2 gC −1 ) from other places. Less than 1% of the aqueous extracts absorption is attributed to the light-absorbing chromophores (nitroaromatic compounds) identified in this work. To identify the major sources of BrC absorption in RTP in the summer, Positive Matrix Factorization (PMF) was applied to a dataset containing optical properties and chemical compositions of carbonaceous components in PM2.5 . The results suggest that the formation of biogenic secondary organic aerosol (SOA) containing organosulfates is an important BrC source, contributing up to half of the BrC absorption in RTP during the summertime. Graphical abstract: Image 1 Highlights: BrC absorption in summer at RTP, NC is similar to other Southeastern US locations. Less than 1% of BrC absorption is attributed to identified nitroaromatic compounds. Biomass burning is not the dominant source for BrC absorption in summer at RTP, NC. Biogenic secondary organic aerosol formation is a major BrC source in this work. Abstract : This study identified a linkage between atmospheric BrC and biogenic SOA formation when biomass burning is not significant in Research Triangle Park, NC during the summer.